Rwanda Climate Services for Agriculture: Evaluation of farmers’ awareness, use and impacts - Birachi, Eliud Abucheli; Hansen, James; Radeny, Maren A.O.; Mutua, Mercy M.; Mbugua, Mercy W.; Munyangeri, Yvonne; Rose, Alison; Chiputwa, Brian; Solomon, Dawit; Zebiak, Stephen E.; Kagabo, Desire M; Nsengiyumva, Gloriose (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate services are important in helping smallholder farmers manage climate-related risks and adapt to climate change, especially for rainfed agricultural production systems. In order to increase the resilience of farmers to the changing climate in Rwanda, the United States Agency for International Development (USAID) funded a four-year project—Rwanda Climate Services for Agriculture (RCSA) from 2016 to 2019. Through the project, climate services were disseminated directly to more than 111,000 farmers in four provinces across Rwanda through Participatory Integrated Climate Services for Agriculture (PICSA), Radio Listeners Clubs (LCs) and cell phones; as well as broadcast by a radio network accessible to about 70% of the population. This report presents analyses of the project end-line survey of 1525 households, sampled across 15 of Rwanda’s 30 districts, in order to assess the influence of PICSA training and LCs on awareness, access and uptake of climate services by smallholder farmers; and their impact on household welfare (i.e., crop productivity, income, food security) on a quasi-experimental sampling design with a non-participant control sample. Analyses show that farmers use climate services to make decisions on the types of crops to grow (75%), the types of crop varieties to plant (58%), timing of planting and land preparation (75%) and when and how to prepare land (65%). Participation in PICSA and LCs, alone and in combination, is associated with a substantial increase in the proportion of farmers that report changing crop, livestock and livelihood management practices in response to weather and climate information. Relative to the control, PICSA participation increased the value of crop production by 24%, and income from crops by 30%. The combination of PICSA and LCs was associated with a 47% increase in the value of crop production, and a 56% increase in income from crops.